2022
DOI: 10.1265/ehpm.22-00136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest bathing (shinrin-yoku) on serotonin in serum, depressive symptoms and subjective sleep quality in middle-aged males

Abstract: Background: We previously found that a forest bathing (shinrin-yoku) program significantly reduced the scores for depression, anxiety, anger, fatigue, and confusion and increased the score for vigor in the profile of mood states (POMS) test and showed a potential preventive effect on the depressive status in both males and females. In the present study, we investigated the effects of a forest bathing program on the level of serotonin in serum, depressive symptoms and subjective sleep quality in middle-aged mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Three studies investigated the effect of Shinrin-yoku on sleep [3,46,48,49]. We previously found that Shinrin-…”
Section: Effect Of Shinrin-yoku On Sleepmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies investigated the effect of Shinrin-yoku on sleep [3,46,48,49]. We previously found that Shinrin-…”
Section: Effect Of Shinrin-yoku On Sleepmentioning
confidence: 99%
“…In addition, forest bathing is particularly effective against mental stress (mental fatigue) [ 3 ]. Li et al [ 46 ] reported that Shinrin-yoku significantly increased level of serotonin in serum, and significantly increased the score for vigor and decreased the score for fatigue in the POMS test. Furuyashiki et al [ 47 ] conducted a comparative study of the physiological and psychological effects of a day-long session of Shinrin-yoku on working age people with and without depressive tendencies and demonstrated significant positive effects on mental health, especially in those with depressive tendencies.…”
Section: Evidence-based Forest Medicinementioning
confidence: 99%
See 3 more Smart Citations